Effects of a high-intensity interval training protocol based on functional exercises on performance and body composition in handball female players - Alonso-Fernández, D.; Lima-Correa, F.; Gutierrez-Sánchez, A.; Abadia-Garcia de Vicuña, O. (Journal of Human Sport & Exercise, 2017)
The aim of this study is to measure the impact of 8-week high-intensity interval training (HIIT) based on functional exercises on the following variables in handball female players: weight (kg), body mass index (BMI), % fat, jumping (cm), repeated sprint ability (RSA), aerobic capacity. Fourteen female players were randomly assigned either to an experimental group (GE, n=7) which would undertake a "mixed functional HIIT" (combining strength, coordination and plyometric exercises) before training sessions, or to a control group (GC, n=7), in which HIIT was replaced by usual warm-up exercises in the field. The intervention programme lasted 8 weeks, with two training sessions a week. A pre-test and post-test on each variable were carried out. The intra-group GC analysis showed no significant changes between the pre- and post-test in any variable. Figures for the GE, though, showed significant changes: a 3.45% (d=0.67) reduction in % fat of players, RSA execution time went down by 7.22% RSA (d=0.82), and VO2max increased by 6.19% (d=0.78). These results seem to point to "mixed functional HIIT" as an effective strategy to improve body composition and performance in female handball players.